Role of Activating Transcription Factor 3 (ATF3) in Endoplasmic Reticulum (ER) Stress-induced Sensitization of p53-deficient Human Colon Cancer Cells to Tumor Necrosis Factor (TNF)-related Apoptosis-inducing Ligand (TRAIL)-mediated Apoptosis through Up-regulation of Death Receptor 5 (DR5) by Zerumbone and Celecoxib - Edagawa, Makoto; Kawauchi, Junya; Hirata, Manabu; Goshima, Hiroto; Inoue, Makoto; Okamoto, Tatsuro; Murakami, Akira; Maehara, Yoshihiko; Kitajima, Shigetaka (The Journal of biological chemistry, 2014)
Death receptor 5 (DR5) is a death domain-containing transmembrane receptor that triggers cell death upon binding to its ligand, TNF-related apoptosis-inducing ligand (TRAIL), and a combination of TRAIL and agents that increase the expression of DR5 is expected to be a novel anticancer therapy. In this report, we demonstrate that the stress response gene ATF3 is required for endoplasmic reticulum stress-mediated DR5 induction upon zerumbone (ZER) and celecoxib (CCB) in human p53-deficient colorectal cancer cells. Both agents activated PERK-eIF2α kinases and induced the expression of activating transcription factor 4 (ATF4)-CCAAT enhancer-binding protein (C/EBP) homologous protein, which were remarkably suppressed by reactive oxygen species scavengers. In the absence of ATF3, the induction of DR5 mRNA and protein was abrogated significantly, and this was associated with reduced cell death by cotreatment of TRAIL with ZER or CCB. By contrast, exogenous expression of ATF3 caused a more rapid and elevated expression of DR5, resulting in enhanced sensitivity to apoptotic cell death by TRAIL/ZER or TRAIL/CCB. A reporter assay demonstrated that at least two ATF/cAMP response element motifs as well as C/EBP homologous protein motif at the proximal region of the human DR5 gene promoter were required for ZER-induced DR5 gene transcription. Taken together, our results provide novel insights into the role of ATF3 as an essential transcription factor for p53-independent DR5 induction upon both ZER and CCB treatment, and this may be a useful biomarker for TRAIL-based anticancer therapy. Background: Death receptor 5 (DR5) triggers cell death upon binding to its ligand TRAIL. Results: ATF3 promotes DR5 induction and apoptotic cell death upon zerumbone or celecoxib treatment in human p53-deficient colorectal cancer cells. Conclusion: ATF3 is an essential transcription factor for p53-independent DR5 induction through the ROS-ER stress pathway. Significance: ATF3 may be a useful biomarker for TRAIL-based anticancer therapy.